STRATEGI PEMASARAN DIGITAL BERBASIS DESAIN VISUAL PENGGUNAAN CANVA PADA PRODUK UMKM PONDOK TANI KABUPATEN SAMOSIR - Erika Rezky Hasanah; Putri Novia Triayu; M. Ridwan Lubis; Rahmat Ibrahim Dalimunthe; Abdi Mubarak Syam (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This paper discusses the implementation of a visual design-based digital marketing strategy using the Canva platform to improve the competitiveness of Pondok Tani MSME products in Samosir Regency. Through community service activities structured in four stages: problem analysis, design planning, design implementation, and evaluation and monitoring, the team helps business owners improve the packaging of traditional products such as bandrek, sasagun, and tipa-tipa to make them more attractive and professional. This approach aims to strengthen product identity, increase visual appeal, and support effective digital marketing, so that local products can be more easily recognized and compete in national and online markets. The evaluation shows that this collaboration not only improves packaging quality but also increases business owners' understanding of the design and digital marketing process, and encourages the sustainability of local culture-based product development.